Pengaruh Diet Anti-Inflamasi Terhadap Penurunan Intensitas Dismenore Pada Remaja Putri: Studi Kuasi-Eksperimental - Jusni; Husnul Khatimah; Kurniati Akhfar; Sumarni; Arfiani (LPPM STIKES Marendeng Majene, 2026)
Dysmenorrhea, or menstrual pain, is a reproductive health issue frequently experienced by adolescent girls. This condition can disrupt daily activities and reduce quality of life. One non-pharmacological approach studied for reducing dysmenorrhea intensity is the anti-inflammatory diet—an eating pattern rich in omega-3 fatty acids, fiber, and antioxidants. This study aimed to determine the effect of an anti-inflammatory diet on reducing dysmenorrhea intensity among adolescent girls. A quasi-experimental design with a non-randomized control group approach was employed. The sample consisted of 20 respondents divided into two groups: a control group and an experimental group that received the anti-inflammatory diet intervention. Data were collected using a Food Frequency Questionnaire (FFQ) and the Numerical Rating Scale (NRS) for pain. Data analysis was performed using the Independent Sample t-test. The results showed that the majority of respondents in both groups experienced moderate dysmenorrhea prior to the intervention (80%). Following the intervention, the experimental group demonstrated a reduction in dysmenorrhea intensity, whereas the control group showed no significant change. Paired Sample t-test results indicated a significant reduction in dysmenorrhea intensity in the experimental group (p < 0.001), but not in the control group (p = 0.468). Independent Sample t-test results revealed a significant difference between the experimental and control groups after the intervention (p = 0.034). Thus, it can be concluded that an anti-inflammatory diet influences the reduction of dysmenorrhea intensity in adolescent girls. This dietary intervention can serve as an alternative non-pharmacological management strategy for addressing menstrual pain.